Performance of Mastication in Menopausal Women in Palembang - Putri Bintang Pamungkas; Shanty Chairani; Rani Purba (Jurnal Kesehatan Gigi, 2019)
Mastication is the mechanical process of breaking down food in oral cavity. The mastication system involves several components, including saliva and alveolar bone. Salivary flow rate and alveolar bone mineral density have been reported decreased in menopausal women due to the impact of declining estrogen levels. Menopause is the permanent cessation of menstruation resulting from the loss of ovarian follicular activity. The aim of this study was to evaluate the masticatory performance in menopausal women in Kelurahan Talang Kelapa RW 19. This observational experimental study with cross-sectional design involved 36 women, consisting of 18 women and 18 non-menopause women. Masticatory performance was evaluated using a sieve method. Each subject was asked to chew 3 gram peanuts for 20 masticatory strokes, which that procedure was repeated for five times. Masticatory performance was measured using a sieve method which based on the assessment of the size of food particles that have been chewed and filtered over a number 10 mesh sieve. Percentage masticatory performance was obtained by dividing volume of particles passed through the filter with the volume of total particles. The masticatory performance data were analyzed statically with independent samples T test. The mean masticatory performance score was 13,71%, in menopausal women and 30,62% in non-menopausal women. It was found that masticatory performance in menopausal women was significantly lower when compared to non-menopausal women (p0,05). It may be concluded that menopause decreased the masticatory performance.